ANALISIS KESIAPAN BELAJAR SISWA KELAS IV UNTUK MEMPELAJARI VOLUME BANGUN RUANG MELALUI INSTRUMEN HUKUM KEKEKALAN VOLUME - Yuni Faujiah; Karlimah; Tb. Moh. Irma Ari Irawan (Jurnal Pendidikan Dasar, 2026)
This study aims to analyse how well fourth-grade elementary school students understand the concept of the volume of three-dimensional shapes, based on the three principles of the law of conservation of volume: identity, reversibility and compensation. A descriptive qualitative approach was employed, with purposive sampling used to select participants representing diverse cognitive abilities. The research instrument was developed based on three fundamental principles of conservation; identity, reversibility, and compensation—derived from Piagetian theory. Data collection was conducted through classroom observations, activity-based tasks using concrete materials, and semi-structured interviews designed to explore students’ reasoning processes. The collected data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that most students have begun to understand the principle of identity, recognizing that quantity remains constant despite changes in form. However, considerable difficulties were observed in the principles of reversibility and compensation. Many students tended to rely on visual perception, such as the height of a substance, rather than conceptual reasoning when evaluating volume changes. These results suggest that students’ readiness to learn volume concepts has not yet developed optimally and remains at a limited conceptual level. This study highlights the importance of identifying students’ cognitive readiness prior to introducing formal mathematical concepts. The use of a volume conservation-based instrument provides deeper insights into students’ thinking patterns and demonstrates its potential as an effective diagnostic tool. Therefore, mathematics instruction should begin with concrete experiences that support conceptual understanding before transitioning to formal procedures